POTENSI INTERAKSI OBAT BISOPROLOL PADA PASIEN BPJS RAWAT JALAN DI POLI JANTUNG RUMAH SAKIT AL HUDA BANYUWANGI - Rosida hari; Dyan Maulani (AKADEMI FARMASI JEMBER, 2022)
Cardiovascular desease become one of the main health problems in developed and developing countries. Cardiovascular patients generally occur in old age who have experienced decreased organ function and complications. They get prescriptions containing more than one type of drug so that spur the possibility of drug interactions. The most commonly prescribed cardiovascular drug is bisoprolol with combination. The study aimed to determinate of potential interactions of bisoprolol drugs in the prescription of outpatient patients at Al Huda Banyuwangi Hospital’s heart poly. This research was a descriptive study conducted retrospective on the BPJS recipe from January to March 2022. Data retrieval techniques were performed randomly which will then be studied theoretically based on literature. The results of 138 prescriptions taken random sampling included 125 prescriptions that had drug interactions. Of the 125 prescriptions there were 276 potential incidents of drug interactions with bisoprolol, based on the severity of major events of 13 (4.71%), moderate 253 (91.67%), and minor 10 (3.62%). The most interacting cardiovascular drug with bisoprolol was ISDN with an interaction of 47 events (17%) with the severity of moderate (strict monitors) that had an effect on increased hypotension effects, followed by aspirin as much as 37 events (13.4%) with the severity of moderate.